Mechanical activation of smectite-based nanocomposites for creation of smart fertilizers - Rudmin, Maxim; Banerjee, Santanu; Makarov, Boris; Ibraeva, Kanipa; Konstantinov, Alexander (Applied sciences)
This research presents the mechanical creation of smart fertilizers from a mixture of smectite and urea in a 3:2 ratio by using the planetary milling technique. The smectite-urea composites show intercalation between urea and mineral, which increases steadily with increasing activation time. A shift of X-Ray Diffraction basal reflections, intensities of Fourier transform infrared spectroscopy (FTIR) peaks, and weight losses in thermogravimetric analysis (TG) document the systematic crystallo-chemical changes of the composites related to nitrogen interaction with activation. Observations of the nanocomposites by scanning electron microscopy (SEM) and transmission electron microscopy (TEM) corroborate the inference. Nitrogen intercalates with smectite in the interlayer space and remains absorbed either within micro-aggregates or on the surface of activated smectites. Soil leaching tests reveal a slower rate of nitrogen than that of traditional urea fertilizers. Different forms of nitrogen within the composites cause their differential release rates to the soil. The formulated nanocomposite fertilizer enhances the quality and quantity of oat yield.